Reconstruction of endometrium from human endometrial side population cell lines. - Irene Cervelló; Aymara Mas; Claudia Gil-Sanchis; Laura Peris; Amparo Faus; Philippa T K Saunders; Hilary O D Critchley; Carlos Simón (PLoS ONE)
Endometrial regeneration is mediated, at least in part, by the existence of a specialized somatic stem cell (SSC) population recently identified by several groups using the side population (SP) technique. We previously demonstrated that endometrial SP displays genotypic, phenotypic and the functional capability to develop human endometrium after subcutaneous injection in NOD-SCID mice. We have now established seven human endometrial SP (hESP) cell lines (ICE 1-7): four from the epithelial and three from the stromal fraction, respectively. SP cell lines were generated under hypoxic conditions based on their cloning efficiency ability, cultured for 12-15 passages (20 weeks) and cryopreserved. Cell lines displayed normal 46XX karyotype, intermediate telomerase activity pattern and expressed mRNAs encoding proteins that are considered characteristic of undifferentiated cells (Oct-4, GDF3, DNMT3B, Nanog, GABR3) and those of mesodermal origin (WT1, Cardiac Actin, Enolase, Globin, REN). Phenotype analysis corroborated their epithelial (CD9+) or stromal (vimentin+) cell origin and mesenchymal (CD90+, CD73+ and CD45⁻) attributes. Markers considered characteristic of ectoderm or endoderm were not detected. Cells did not express either estrogen receptor alpha (ERα) or progesterone receptor (PR). The hESP cell lines were able to differentiate in vitro into adipocytes and osteocytes, which confirmed their mesenchymal origin. Finally, we demonstrated their ability to generate human endometrium when transplanted beneath the renal capsule of NOD-SCID mice. These findings confirm that SP cells exhibit key features of human endometrial SSC and open up new possibilities for the understanding of gynecological disorders such as endometriosis or Asherman syndrome. Our cell lines can be a valuable model to investigate new targets for endometrium proliferation in endometriosis.